Design, synthesis, and biological evaluation of 3-vinyl-quinoxalin-2(1H)-one derivatives as novel antitumor inhibitors of FGFR1 - Liu Z; Yu S; Chen D; Shen G; Wang Y; Hou L; Lin D; Zhang JS; Ye F (Dove Medical Press, 2016)
Zhiguo Liu,1,* Shufang Yu,1,* Di Chen,1 Guoliang Shen,1 Yu Wang,1 Leping Hou,2 Dan Lin,1 Jinsan Zhang,1 Faqing Ye1 1School of Pharmaceutical Sciences, Wenzhou Medical University, Wenzhou, 2Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, People’s Republic of China *These authors contributed equally to this work Abstract: FGFR1 is well known as a molecular target in anticancer drug design. TKI258 plays an important role in RTK inhibitors. Utilizing TKI258 as a lead compound that contains a quinazolinone nucleus, we synthesized four series of 3-vinyl-quinoxalin-2(1H)-one derivatives, a total of 27 compounds. We further evaluated these compounds for FGFR1 inhibition ability as well as cytotoxicity against four cancer cell lines (H460, B16-F10, Hela229, and Hct116) in vitro. Some compounds displayed good-to-excellent potency against the four tested cancer cell lines compared with TKI258. Structure–activity relationship analyses indicated that small substituents at the side chain of the 3-vinyl-quinoxalin-2(1H)-one were more effective than large substituents. Lastly, we used molecular docking to obtain further insight into the interactions between the compounds and FGFR1. Keywords: FGFR1, synthesis, quinoxaline, antitumor activity, kinase inhibitor